Teater sebagai Media Komunikasi Lingkungan: Studi Kasus pada Pertunjukan Teater Kafha Re(kognisi) - Farah Novda Rahmadani; Ahmad Mulyana (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to explore the creative process of the Teater Kafha team in raising stakeholder awareness regarding environmental issues through the theater performance